(untitled) (Bangladesh Journal of Infectious Diseases, 2023)
Background: Urinary tract infection is caused by different bacteria of family enterobacteriaceae in the hospital and community acquired infection. Objective: The purpose of the present study was to find out the bacteria causing urinary tract infection, frequency as well as their antibiotic resistance pattern. Methodology: This cross-sectional study was conducted in the Department of Microbiology at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from June 2017 to November 2017 for a period of six months. Different urine samples of patient who were presented with infection in the urinary tract were included as study population. Using sterile container urine samples were taken from both IPD and OPD patients of National Institute of Neurosciences and Hospital, Dhaka, Bangladesh. The urine specimen was inoculated on blood and MacConkey agar plates and incubated at 37°C for 24 hours. Identification was based on standard microbiological methods The antibiogram testing was done by using modified Kirby-Bauer method. Results: A total of 200 urine samples were included for study of which 118(59%) cases showed positive and 82(41.0%) cases showed negative growth. Among 118 samples Escherichia coli were in 56(47.5%) isolates followed by Klebsiella pneumoniae were in 22(18.6%); Citrobacter freundii were in 20(16.9%); Pseudomonas species were 12(10.2%) and Proteus mirabilis were 8(6.8%). Escherichia coli was most predominant urinary tract infection causing species (47.5%) and found most resistant against cefixime (96.4%), azithromycin (92.9%), ciprofloxacin (71.4%); Klebsiella pneumonia was most resistant to amikacin, azithromycin (81.82%), ciprofloxacin, tazobactum/piperacillin (72.7%) cefixime, meropenem (63.7%). Citrobacter freundii was resistance to ciprofloxacin, cefixime (80.0%). Conclusion: Escherichia coli infections are more common in urinary tract infection patients and predominant resistant against cefixime followed by Klebsiella pneumonia. Bangladesh Journal of Infectious Diseases, December 2022;9(2):47-52